Population differences in putty-nosed monkey (Cercopithecus nictitans) call order - Mehon, Frederic Gnepa; Zuberbühler, Klaus; Stephan, Claudia (Primates, 2024)
Non-human primates generally lack the ability to learn new call structures or to substantially modify existing ones, suggesting that callers need alternative mechanisms to convey information. One way to escape the constraints of limited vocal control is by assembling calls into variable sequences, as has been documented in various animal species. Here, we were interested in the flexibility with which different calls might be assembled in a species known for its meaningful call order, putty-nosed monkeys (Cercopithecus nictitans). Since most information comes from studies conducted at Gashaka Gumti National Park (Nigeria), we tested two further populations in the Nouabalé-Ndoki National Park (Republic of the Congo) and Taï National Park (Côte d’Ivoire) in how males responded to common threats, leopards, and crowned eagles. As predicted, callers produced the same basic call types as seen elsewhere—long ‘pyow’, short ‘pyow’ (‘kek’), ‘hack’—but populations differed in how males assembled calls. To leopards, males from both populations started with ‘pyows’ and ‘keks’, with occasional hacks later, as already reported from Gashaka. To crowned eagle, however, Nouabalé-Ndoki males consistently initiated their responses with ‘pyows’, whereas neither Taï nor Gashaka males ever did, demonstrating that nonhuman primates have some control over sequence production. We discuss possible mechanisms to account for the population differences, predation pressure, and male–male competition, and address implications for linguistic theories of animal call order, notably the Urgency and Informativity Principles.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Alarm calls; Call compositions; Forest guenons; Informativity Principle